Subcellular mass spectrometry reveals proteome remodeling in an asymmetrically dividing (frog) embryonic stem cell - Bowen Shen; Leena R. Pade; Fei Zhou; Peter Nemes (Proceedings of the National Academy of Sciences, 2026)
Subcellular proteomics maps protein localization within restricted domains of a cell, complementing high-resolution imaging by expanding the number of proteins that can be profiled at once. Achieving this at depth from subcellular inputs remains challenging. Here, we advance microprobe capillary electrophoresis–mass spectrometry (CE–MS) with trapped ion mobility spectrometry and data-independent acquisition (diaPASEF) to quantify more than a thousand proteins from opposite poles of an asymmetrically dividing embryonic blastomere in live Xenopus laevis embryos. From ~200 pg of HeLa digest—approximately 80% of a cell—the technology identified 1,035 proteins with high reproducibility in quantification (coefficient of variation <15% across technical triplicates). With microprobe sampling in vivo, we quantified 808–1,022 proteins from opposite poles of the dorsal–animal (D1) blastomere before division, and we traced how these spatial distributions are retained or remodeled in the descendant D1.1 (neural-fated) and D1.2 (epidermal-destined) cells. To decouple subcellular distributions from dorsal–ventral axis cues, we perturbed patterning by ultraviolet ventralization. These results establish microprobe CE–MS for deep subcellular proteomics in intact embryos and reveal spatially distinct protein distributions during early fate specification. These spatial proteome differences appear consistent with early lineage tendencies yet precede and likely bias, rather than fix, later fate decisions that depend on gastrula-stage inductive signals.